2014
DOI: 10.1002/ca.22387
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular innervation patterns of the brachialis muscle

Abstract: The aim of this study was to provide accurate anatomical descriptions of the patterns of innervation of the brachialis muscle by the musculocutaneous, radial, and median nerves. Sihler's staining method was applied to 20 brachialis muscles from 10 cadavers to reveal the intramuscular distribution patterns of the musculocutaneous, radial, and median nerves. Three patterns of innervation of the brachialis muscle by the three studied nerves were found: single, double, and triple. These innervation patterns were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…The brachial plexus continues to be of significant clinical interest [8][9][10][11][12][13] and thus our current knowledge of this structure was begun by the works of da Vinci in the fifteenth century. …”
Section: Discussionmentioning
confidence: 99%
“…The brachial plexus continues to be of significant clinical interest [8][9][10][11][12][13] and thus our current knowledge of this structure was begun by the works of da Vinci in the fifteenth century. …”
Section: Discussionmentioning
confidence: 99%
“…) and underwent Sihler staining, as modified by Liem and Douwe van Willigen . This method involves many steps to obtain a visual representation of the neural arborization pattern . After completing the Sihler staining, the vertical lengths of the FHL, TP, and FDL were divided into 10 equal divisions by transverse lines, each representing 10% increments of the total length.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies assumed that the MEP zone was located at the center of a muscle belly . However, intramuscular nerve distribution varies within muscles, as revealed by Sihler staining of forearm muscles, hip adductor muscles, and calf muscles . Still, no anatomical studies have been conducted on the tibialis posterior (TP), flexor hallucis longus (FHL), and flexor digitorum longus (FDL), which are the muscles targeted for releasing equinovarus foot and toe clawing…”
mentioning
confidence: 99%
“…Extremely rare cases in which distinct branches of the median nerve supply the inferior portion of the BM have been cited in the literature. Hur et al, [14] observed such a branch originating from the upper edge of the median nerve innervating the infero-medial portion of BM, whereas Won et al, [15] noticed the median nerve supplying the lower quarter of the BM in 15% and the BM's uppermost quarter in 5% of the specimens. Our case, that corresponds to type III according to Won's et al, classification, resembles with that of Hur et al, with the difference of branching site that was located at the limit between middle and inferior portion of the median nerve.…”
Section: Introductionmentioning
confidence: 99%